Spatial dynamics of the Serra do Gandarela and around: an analysis from representations coremáticas - Fonseca, Charles de Oliveira; Valadão, Roberto Célio (Sociedade & Natureza, 2017)
This work employs the chorematic modeling as methodological procedure liable to present the spatio- temporal dynamic of the Gandarela Ridge and surroundings. Such modeling interacts with geographical concepts that once mobilized, become possible the use of analytical categories necessary for understandingspatial organization by means of graphic images. Therefore, the chorems presented aim to transcend theinformation communicated through conventional maps. Opposing to the current economic, mineral andenviromental reality of the Quadrilátero Ferrífero, the Gandarela Ridge is nowadays the latest naturalremaining in good state of repair in this region of Minas Gerais. In the vicinity of this ridge, there are localcommunities that do use areas for subsistence production, collection and extraction. In this scenario, inthe last couple of years, polarized pressure fields have been formed: on one hand mining companies andeucalyptus producers claim the legalization of the land use for their core activities; on the other hand,environmentalists, researchers and local residents, with the support of the ICMBio and NGOs, havepositioned themselves in favour of the creation of the Parque Nacional do Gandarela and a sustainabledevelopment reserve. Those vindications and placements have established territorial pressures that set thecurrent and complex environmental framework of the investigated area, marked by conflicting interests ofmultiple actors and consequently by conflict and spatial changes, registered here in chorematics models.